PENGARUH PROMOSI ONLINE TRAVEL AGENT TERHADAP KEPUTUSAN TAMU MENGINAP DI GRAND BASKO HOTEL PADANG - Sari, Mia Wulan; Pratiwi Wulandari, Dwi (Ensiklopedia of Journal, 2024)
The purpose of this study is to examine how internet travel agency advertising affect travelers' choices to stay at the Grand Basko Hotel Padang. This kind of research uses a quantitative method and is associative descriptive research. The participants in this study were visitors who had stayed at the Grand Basko Hotel Padang between July and December of 2022. A purposive sampling technique was used to select 216 participants for the sample. Based on the study's findings, the following three conclusions are drawn. First, Grand Basko Hotel Padang's internet promotion reveals that the overall percentage value of 37.9% falls into the very good category. Second, choosing to stay at the Grand Basko Hotel Padang is a very good choice, as indicated by the overall percentage figure of 46.76%. So that there is a significant influence between online promotions on guest decisions to stay at Grand Basko Hotel Padang with a total R square value of 0.653. meaning that online promotions have an influence on guest decisions to stay at Grand Basko Hotel Padang by 65.3% while 34.7% is influenced by other factors.Keywords: Online Promotion, Management Decisions